Privileging roots and routes Filipino intellectuals and the contest over epistemic power and authority - Hau, Caroline Sy (Philippine studies : historical and ethnographic viewpoints, 2014)
"Reynaldo Ileto's "Orientalism in the Study of Philippine Politics" (1999) highlighted the problematical relationship between colonialism and knowledge production in American scholarship on the Philippines. In recent decades the target of the critique has shifted to Filipino-American and overseas Filipino intellectuals. This article examines the changing intellectual and material contexts in which Philippine-based, often middle-class, intellectuals claim epistemic privilege in representing the Philippines by vitue of "authentic" experience and knowledge. These claims involve a contest over the power and authority to speak (on behalf) of the Philippines and the role and subject positions of intellectuals in relation to a "Filipino nation" that is in the throes of transformation."